Cost-Effectiveness Analysis of Group vs. Weblog Telecommunication (Web Tel) Nutrition Education Program on Glycemic Indices in Patients With Non-Insulin Dependent Diabetes Mellitus Type 2: A Randomized Controlled Trial - Derakhshandeh-Rishehri, Seyedeh-Masomeh; Keshavarz, Khosro; Ghodsi, Delaram; Pishdad, Gholamreza; Faghih, Shiva (Frontiers in Nutrition, 2022)
This is a cost-effectiveness analysis along with randomized controlled trial study, aimed to compare the cost-effectiveness of Group vs. Web-Tel nutrition education on glycemic control in patients with non-insulin-dependent type 2 diabetes. One-hundred five patients with type 2 diabetes mellitus (T2DM) enrolled in the study. It was conducted for three months in Quds health centre of Bushehr province, Iran. The participants were classified based on the age and disease severity (hemoglobin A1c level), then they were randomly assigned to one of the three groups: Group education, Web-Tel education, and the control group using block randomization method. The clinical (intermediate) outcome was changes in hemoglobin A1c (HbA1c). Patient perspective was adopted, and a deterministic one-way sensitivity analysis was conducted to identify the effects of uncertainties. The results indicated that the expected effectiveness was 0.46, 0.63, and 0.40; and the mean costs were 27188, 5335, and 634 Purchasing Power Parities (PPP) dollars, for Group education, Web-Tel education, and control group, respectively. The incremental cost-effectiveness ratio (ICER) of Web-Tel education versus control group was positive and equal to $21613.04 PPP; since it was less than three times of threshold, Web-Tel education method was considered as a more cost-effective method than control group. On the other hand, the ICER of Group education vs. control group was $447067 PPP and above threshold, so the Group education was considered as a dominated method compared with control group. Considering the incremental cost-effectiveness ratio, Web-Tel education is a more cost-effective method than two other methods and can be used as the first priority in educating the patients with type 2 diabetes. The trial was registered in Thailand Clinical Trials Registry (TCTR20210331001).